Analyses of miRNA in the ileum of diarrheic piglets caused by Clostridium perfringens type C. (November 2019) - Wang, Pengfei; Huang, Xiaoyu; Yan, Zunqiang; Yang, Qiaoli; Sun, Wenyang; Gao, Xiaoli; Luo, Ruirui; Gun, Shuangbao
Abstract: Clostridium perfringens ( C. perfringens ) type C is one of major pathogenic causing diarrhea and other intestinal inflammatory diseases in piglets, which seriously affects the healthy development of the swine industries. Studies have found that miRNAs play important roles in regulating piglet diarrhea challenged by pathogenic E. coli and Salmonella . However, little is known miRNAs in the ileum of diarrheic piglets caused by C. perfringens type C. Therefore, we studied the expression profiles of the ileum miRNAs of 7-day-old piglets infected with C. perfringens type C using small RNA-Seq, including control (IC), susceptible (IS) and resistant (IR) groups. As a result, 53 differentially expressed miRNAs were found. KEGG pathway analysis for target genes revealed that these miRNAs were involved in ErbB signaling pathway, MAPK signaling pathway, Jak-STAT signaling pathway and Wnt signaling pathway. The expression correlation analysis between miRNAs and target genes revealed that the expression of miR-7134-5p had negative correlation with target NFATC4, miR-500 had negative correlation with target ELK1, HSPA2 and IL7R, and miR-92b-3p had negative correlation with target CLCF1 in ileum of IR vs IS group, suggesting that miR-7134-5p targeting to NFATC4, miR-500 targeting to ELK1, HSPA2 and IL7R, and miR-92b-3p targeting to CLCF1 were probably involved in piglet resisting C. perfringens type C. The results will provide value resources for better understanding of the genetic basis of C. perfringens type C resistance in piglet and lays a new foundation for identifying novel markers of C. perfringens type C resistance. Highlights: miRNA expression profiling in the ileum of diarrheic piglets caused by Clostridium perfringens type C. Integrating analysis of miRNA in the ileum of diarrheic piglets caused by Clostridium perfringens type C. Differently expressed miRNAs were probably involved in piglet resisting Clostridium perfringens type C .